PROBLEMATIK KEKERASAN DALAM PANDANGAN AGAMA KRISTIANI | THE PROBLEM OF VIOLENCE IN THE VIEW OF THE CHRISTIAN RELIGION - George Ludwig Kirchberger (Institut Filsafat dan Teknologi Kreatif Ledalero, 2018)
Abstract : This article intends to consider the relationship between violence and the sacred, using as a starting point a theory espoused by Rene Girard. According to this theory, Girard demonstrates that violence happens because human beings imitate others in determining a desired object. Because of that imitation, a conflict arises between those who possess the same object. This conflict is calmed-down by transferring the reciprical aggression onto a specific group that becomes the scape-goat, to be sacrificed. The ritual of sacrifice is institutionalised in religion. In this way, religion can channel aggression, but it can also hide human violence, by exoressing violence towards the person of God. Following on, Christian revelation is pictured as being a process, in which God reveals Godself in a true attitude, and demonstrates that the violence expressed is between human beings and not towards God. In summary, the Christian religion can be a religion of salvation when it truly studies and proclaims a picture of God as revealed in Judeo-Christian revelation, climaxed in the person of Jesus of Nazareth. Keywords: Rene Girard, scape-goat; Jesus as the universal scape-goat; Christian revelation; violence and religion. Abstrak : Artikel ini mau meneliti relasi antara kekerasan dan kekeramatan dengan bertolak dari satu teori yang diciptakan oleh René Girard. Dalam teori itu Girard memperlihatkan kekerasan terjadi, karena manusia meniru orang lain dalam menentukan objek yang diinginkan. Karena peniruan itu, terjadilah konflik antara orang yang memilih objek yang sama. Konflik itu diredakan dengan mengalihkan semua agresi timbal balik dalam suatu kelompok kepada satu kambing hitam yang menjadi korban. Ritual korban itu diinstitusionalisasi dalam agama. Dengan demikian agama bisa menyalurkan agresi, tetapi juga menyembunyikan agresi antara manusia dalam kekerasan pada diri Allah. Selanjutnya wahyu kristiani digambarkan sebagai proses, di dalamnya Allah memperkenalkan diri dalam sikap yang benar dan memperlihatkan, agresi itu ada di antara manusia dan bukan dalam diri Allah. Kesimpulannya, agama kristiani bisa menjadi agama penyelamatan bila secara sungguh mempelajari dan mewartakan gambaran tentang Allah yang dinyatakan dalam wahyu Yahudi-Kristen dengan puncaknya dalam diri Yesus dari Nazaret. Kata kunci: René Girard; teori kambing hitam; Yesus sebagai kambing hitam universal; wahyu kristiani; kekerasan dan agama